Transformation and Innovation of Digital-Based Islamic Boarding School - Masrul Anam; Abdur Rouf Hasbullah (TADRIS: Jurnal Pendidikan Islam, 2026)
Digital transformation in education has become a crucial pillar in addressing the challenges of the Fourth Industrial Revolution. This research aims to explore and analyze the digital transformation process and innovative learning practices at two Islamic boarding schools: Al Aqobah Islamic Boarding School and Sakal Calligraphy School, both located in Jombang. The study also examines how these schools integrate digital technology into their educational systems to enhance the quality of learning and prepare students to meet global challenges. Using a mixed-method approach with a case study design, the research seeks to gain a deeper understanding of the digital transformation process and the digital learning innovations implemented in these Islamic boarding schools. The findings of the study reveal several key points: First, The managers of both Islamic boarding schools possess a positive, inclusive, and transformative perspective. Second, The implementation of digital transformation at both schools involves adopting and integrating digital technology across various aspects of education, tailored to the specific takhassus (specialization) of each Islamic boarding school. This digital transformation has driven the emergence of various innovations within each institution. The integration of digital-based learning and innovations in these Islamic boarding schools is progressing effectively, with an average success rate of 77.60%. Third, further, the digital transformation at these Islamic boarding schools has positively impacted the quality of learning, proven by improved student achievement. An average increase in student performance to 85.00% after adopting a digital-based learning approach. Overall, this study highlights the significant role of digital transformation in enhancing educational practices within Islamic boarding schools